Racial Diversity and Racial Policy Preferences: The Great Migration and Civil Rights - Alvaro Calderon; Vasiliki Fouka; Marco Tabellini (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2021)
Between 1940 and 1970, more than 4 million African Americans moved from the South to the North of the United States, during the Second Great Migration. This same period witnessed the struggle and eventual success of the civil rights movement in ending institutionalized racial discrimination. This paper shows that the Great Migration and support for civil rights are causally linked. Predicting Black inflows with a shift-share instrument, we find that the Great Migration raised support for the Democratic Party, increased Congress members' propensity to promote civil rights legislation, and encouraged pro-civil rights activism outside the US South. We provide different pieces of evidence that support for civil rights was not confined to the Black electorate, but was also shared by segments of the white population.
Keywords: D72; J15; N92; 330; Race; diversity; civil rights; Great Migration